2021
DOI: 10.3390/app112412061
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical and Robotic Devices for Gait and Balance Rehabilitation of Children with Neurological Disability: A Systematic Review

Abstract: In the last two decades, a growing interest has been focused on gait and balance robot-assisted rehabilitation in children with neurological disabilities. Robotic devices allow the implementation of intensive, task-specific training fostering functional recovery and neuroplasticity phenomena. However, limited attention has been paid to the protocols used in this research framework. This systematic review aims to provide an overview of the existing literature on robotic systems for the rehabilitation of gait an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
(138 reference statements)
0
1
0
Order By: Relevance
“…Due to the aforementioned advantages and the importance of balance and gait in ADLs, a wide range of rehabilitation robots has been developed during the last few decades [36]. However, the current literature on rehabilitation robotics often provides limited information about the characteristics of available prototypes, and this lack of information makes the classification of robotic devices challenging [37].…”
Section: Aim Of the Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Due to the aforementioned advantages and the importance of balance and gait in ADLs, a wide range of rehabilitation robots has been developed during the last few decades [36]. However, the current literature on rehabilitation robotics often provides limited information about the characteristics of available prototypes, and this lack of information makes the classification of robotic devices challenging [37].…”
Section: Aim Of the Articlementioning
confidence: 99%
“…Several research and review articles have collated information about end effectors already available for gait and balance rehabilitation [36,46]. However, most of these are part of a classification study that includes other type of rehabilitation devices (exoskeletons, treadmills, stationary trainers, etc.…”
Section: Advantages Of End Effector-type Rehabilitation Devicesmentioning
confidence: 99%
“…Although epidemiological studies have shown that sociodemographic and clinical characteristics of subacute stroke survivors can predict good participation in walking activities in the community 6 months after stroke [7,8], walking recovery must be promoted by targeted intensive rehabilitation programs. In this context, Wearable Powered Exoskeletons (WPEs) could be valuable complementary rehabilitation devices, as they emulate overground human neuromotor control of locomotion, allowing early, intensive, and specific gait training even in individuals unable to maintain the upright position [9]. The efficacy of WPE-assisted gait training to improve motor and functional outcomes in stroke patients is well established in the literature [10][11][12][13][14][15][16][17][18], although the neurophysiological effects have not yet been adequately studied [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%